Characterization of the β-glucuronidase Pn3Pase as the founding member of glycoside hydrolase family GH169. (28th July 2020) - Wantuch, Paeton L; Jella, Satya; Duke, Jeremy A; Mousa, Jarrod J; Henrissat, Bernard; Glushka, John; Avci, Fikri Y
Abstract: Paenibacillus sp. 32352 is a soil-dwelling bacterium capable of producing an enzyme, Pn3Pase that degrades the capsular polysaccharide of Streptococcus pneumoniae serotype 3 (Pn3P). Recent reports on Pn3Pase have demonstrated its initial characterization and potential for protection against highly virulent S. pneumoniae serotype 3 infections. Initial experiments revealed this enzyme functions as an exo-β1, 4-glucuronidase cleaving the β(1, 4) linkage between glucuronic acid and glucose. However, the catalytic mechanism of this enzyme is still unknown. Here, we report the detailed biochemical analysis of Pn3Pase. Pn3Pase shows no significant sequence similarity to known glycoside hydrolase (GH) families, thus this novel enzyme establishes a new carbohydrate-active enzyme (CAZy) GH family. Site-directed mutagenesis studies revealed two catalytic residues along with truncation mutants defining essential domains for function. Pn3Pase and its mutants were screened for activity, substrate binding and kinetics. Additionally, nuclear magnetic resonance spectroscopy analysis revealed that Pn3Pase acts through a retaining mechanism. This study exhibits Pn3Pase activity at the structural and mechanistic level to establish the new CAZy GH family GH169 belonging to the large GH-A clan. This study will also serve toward generating Pn3Pase derivatives with optimal activity and pharmacokinetics aiding in the use of Pn3Pase as a novel therapeutic approach against type 3 S. pneumoniae infections.